Culture and Power in the Reconstitution of the Chinese Realm, 200-600 - Ebrey, Patricia Buckley, 1947-; Spiro, Audrey G.; Pearce, Scott (Book collections on Project MUSE., 2001)
"China's early medieval age - the time between the fall of the Han in A.D. 220 and the Sui's reunification of the realm in 589 - receives short shrift in most accounts of Chinese history, which typically characterize it in negative fashion as an age of disorder and dislocation, ethnic strife and bloody court battles, an era whose only notable achievement was the introduction of Buddhism. But despite the violence and volatility, these centuries were a time of extraordinary cultural flowering, which reshaped and deeply enriched Chinese civilization. Culture and cultural change are the primary focuses of the eight essays in this volume." "The authors of these essays address the growth of cities, literary theory, the civil service examinations, Buddhist art, governmental reform, Daoism, and literary anthologies. Although they take diverse viewpoints as they seek to chart the changes that unfolded across the early medieval age, their work is bound together by several overarching themes: evolving notions of the nature of the center and its relationship to the periphery, of boundaries between groups and regions: ideas of order and the re-creation of order; and views on connections to the past and the significance of historical inheritance. These are issues that were central to the work of reconstituting a Chinese realm that was both culturally and politically coherent."--Jacket.